Модернізація інформаційного ресурсу засобами CMS WordPress - Семеренко, Лілія; Федушко, Соломія (Видавництво Львівської політехніки, 2018)
Development of information technology is the most important area of knowledge and social relations. Website for students is a highly effective way of communication and sharing of experiences.
Keywords: інформаційний ресурс; WordPress; CMS; системи керування вмістом